Characteristic and psychosocial consequences of sexually abused children referred to a tertiary care facility in Oman: Sentinel study. Issue 1 (January 2020) - Alshekaili, Muna; Alkalbani, Yahya; Hassan, Walid; Alsulimani, Fatima; Alkasbi, Salim; Chan, Moon Fai; Al-Adawi, Samir
Abstract: Background: Child Sexual Abuse (CSA) has been reported from different parts of the world. With regard to countries in the Arabian Gulf, there have been some anecdotal and impressionistic observations of CSA and Oman is no exception. Aims: In order to lay the groundwork for empirical scrutiny of this phenomena, the present study elaborates on the description of the CSA along with exploring the socio-demographic and psychosocial consequences among children with a history of sexual abuse referred to a tertiary care center providing mental services catering to the needs of children and adolescents mental health services (CAMHS). Method: 34 children referred for a one-year period to the CAMHS fulfilled the criteria for inclusion of the study. Socio-demographic, CSA, and psychosocial information were collected for each subject. Chi-square test, Fisher's exact test, and multiple logistic regression analysis was used to explore which variables associated with children having depressive symptoms. Result: Majority of children abused were female (64.7%, n = 22), age below 12 years (67.6%, n = 23), and with low family income (85.3%, n = 29). Multivariate analysis shows that CSA and psychological variables were significant risk factors for depression. Children who were penetrative abused were more likely (OR = 24.897, p = 0.044) to have depression than non-penetrative children. Children who reported problems with sleep-wake cycles (OR = 44.636, p = 0.012) were more likely to occurrence of depressive symptoms than children who reported no such problem. Conclusion: The patterns of CSA and its consequences in Oman appears to echo the trends from other parts of the world. As the country is becoming increasingly aware of the international best practice towards CSA, this study will serve as a milestone for more studies in the area using robust methodology. Abstract : Psychology; Child sexual abuse; Psychosocial factors; Consequences; Depression; Oman.